Quantitative Study: Multimedia-Assisted SAVI Learning Model and Its Impact on Mathematical Problem-Solving Ability - Gunawan Gunawan; Fanni Yunita (Pendidikan Matematika STKIP Kusuma Negara, 2025)
In the 21st century, education focused on equipping students with abilities for lifelong learning and self-development, one of which was problem-solving ability. This ability was crucial in preparing students to solve real-life problems. The SAVI (Somatic, Auditory, Visual, Intellectual) learning model was one of the instructional models that could enhance students' mathematical problem-solving ability and could be integrated with technology use. This study aimed to examine the effect of the SAVI learning model assisted by multimedia on students' mathematical problem-solving ability. This research was a quasi-experimental study using the non-equivalent posttest only control group design. The sample consisted of classes X-1 and X-2 from a public high school in Magelang. The sample was selected by random sampling technique. The data obtained were processed using Independent Sample t–test and effect size. The results of the data analysis showed that there was a significant difference in students' mathematical problem-solving ability between the control and experimental groups. In addition, an effect size of 0.7 was obtained, indicating that the SAVI learning model assisted by multimedia had a large impact on mathematical problem-solving ability. This study recommended broader implementation and exploration in other subjects to enhance learning effectiveness.